2014
DOI: 10.1155/2014/902734
|View full text |Cite
|
Sign up to set email alerts
|

Ficus deltoidea Jack: A Review on Its Phytochemical and Pharmacological Importance

Abstract: Ficus deltoidea Jack (Moraceae) has had a long history of use in traditional medicine among the Malays to alleviate and heal ailments such as sores, wounds, and rheumatism and as an after-birth tonic and an antidiabetic drug. Modern pharmacological studies demonstrated that this plant has a wide variety of beneficial attributes for human health. Despite its importance, a review of this species has not been published in the scientific literature to date. Here, we review and summarize the historic and current li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 24 publications
1
70
0
Order By: Relevance
“…A wide range of chemical compounds have been isolated and characterized from F. deltoidea, particularly from the leaves and figs [5]. An initial comprehensive study 2009) isolated and identified moretenol from F. deltoidea leaves using nuclear magnetic resonance (NMR) and mass spectrometers [18].…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of chemical compounds have been isolated and characterized from F. deltoidea, particularly from the leaves and figs [5]. An initial comprehensive study 2009) isolated and identified moretenol from F. deltoidea leaves using nuclear magnetic resonance (NMR) and mass spectrometers [18].…”
Section: Resultsmentioning
confidence: 99%
“…Those two species not only have been used as medicines for various ailments in the Malay Archipelago, but also pharmaceutically tested to have medicinal chemical compounds (see Table 5). Eurycoma longifolia and Ficus deltoidea have been distributed and formulated as capsules, tea, and tonic tea throughout Malaysia (Bunawan, Amin, Bunawan, Baharum, & Noor, 2014;Effendy, Mohammed, Muhammad, Mohammad, & Shuid, 2012). The species Arbus precatorius that is used to make easy and smooth the childbirth by the Kutai people in Menamang villages also used for the same efficacy in Guinea-Bissau and Ivory Coast.…”
Section: Species Identification Of Traditional Medicinal Plants Used mentioning
confidence: 99%
“…6,7 An anticancer research that was conducted to ovarian cancer cell lines, in vitro showed IC 50 values of 224.39 ± 6.24 pg/mL for FD aqueous extract and 143.03 ± 20.21 pg/mL forFD ethanolic extract. 2,8 A more extensive study on FD anticancer potential with other types of cancer, both in vitro and in vivo, needs to be performed. In Indonesia, colon cancer is the third most common cancer diagnosed after cervical and breast cancer.…”
Section: Introductionmentioning
confidence: 99%